Emergence of nitrosourea resistant sublines of Lewis lung tumour following MeCCNU treatment in vivo. - Stephens, T. C. (Nature Publishing Group, 1986)
Several different drug retreatment protocols were employed to examine the emergence of resistance to MeCCNU in Lewis lung tumours. Previous studies suggested that although the majority of cells in untreated Lewis lung tumours were sensitive to MeCCNU, there was a very small proportion of resistant cells (approximately 0.001%) that limited "tumour cure' with that drug. If such cells were inherently drug resistant then it should be possible to derive highly resistant tumours by repeated drug treatment. In the first experiment tumours were treated with a single high dose of MeCCNU (35 or 40 mgkg-1) and on regrowth, transplanted into fresh mice and tested for drug sensitivity. Using both excision cell survival and growth delay endpoints, only approximately 25% of tumours were significantly resistant to the test dose, suggesting that many tumours resist the effects of the drug for reasons other than the presence of inherently drug resistant cells. One of the tumours (R4), that regrew after the initial treatment and appeared to be resistant to the test treatment, was retreated with a further 30 mgkg-1 MeCCNU and became more resistant. This line, designated R4/1, was cross-resistant to the other nitrosoureas, BCNU and CCNU, but not to cyclophosphamide, melphalan, cis-platinum or ionising radiation. The effect of treatment dose on the kinetics of MeCCNU resistance development was also studied in a retreatment regimen where the tumours were allowed to regrow and then transplanted into fresh hosts for the next treatment. Resistance developed more quickly at an intermediate dose of 15 mgkg-1 than at 7.5 mgkg-1 where the selective pressure was lower, or at 30 mgkg-1 where there was probably extinction of partially resistant cells. Resistance to MeCCNU developed even more quickly when tumours were retreated several times in the same host, although in a similar experiment with cyclophosphamide no resistance occurred.